Patron-client dynamics in Flavius Josephus' "Vita": A cross-disciplinary analysis. - Strangelove, Michael. (University of Ottawa (Canada), 1992)
Throughout history, Flavius Josephus has been the victim of character assassinations carried out by Jews, Christians and modern scholars alike. This thesis uses the methodology of social scientific analysis to compile a model of patron-client relations from the disciplines of sociology, anthropology, political science, and ancient history. This eclectic model is then applied to Josephus' autobiography, the Vita, in an effort to arrive at a culturally sensitive understanding of the social personality of Josephus as a patron of the Galileans. Patron-client dynamics are uncovered in four groups of relational encounters: (1) Josephus, Poppea Sabina and Aliturus; (2) Josephus and John of Gischala; (3) Josephus and the Galileans; and (4) Josephus and Vespasian, Titus, Domitian and Epaphroditus. The results of this modelling process are contrasted against the results of the dominant historical methodology, with particular attention being given to the conclusions of Shaye J. D. Cohen's Josephus in Galilee and Rome: His Vita and Development as a Historian, (Leiden: Brill, 1979). It is demonstrated that patron-client relations are a significant factor within the Vita and the application of a model of patron-client relations serves to eliminate ethnocentric judgements that have been erroneously applied to both the text and its author.
Keywords: Biography.